Corporate Finance and Governance - Goh, Jeremy C (Institutional Knowledge at Singapore Management University, 2014)
Finance and Financial Markets is one of Singapore Management University's (SMU) identified areas of excellence, or AoE, launched to project the university's distinctive academic leadership in this field. The Finance and Financial Markets AoE creates value for a diverse range of stakeholders through integrating multidisciplinary research, teaching and knowledge transfer, and outreach and collaboration. It encompasses a wide spectrum of topics within the finance domain, as well as its applications in various aspects of financial markets. Associate Professor Jeremy Goh from SMU’s Lee Kong Chian School of Business is a well-published finance academic and has written numerous articles in international research publications, including prestigious journals such as the Journal of Finance, Journal of Business and Financial Analysts Journal. In this podcast, Associate Professor Goh shares his research and expertise in Corporate Finance and Corporate Governance. Also the Programme Director of the Citi-SMU Financial Literacy Programme for Young Adults, he shares his involvement in equipping young adults with essential personal finance knowledge and skills, to give them a firm foundation in managing their money and a financial head-start early in their working lives.